Race, National Identity, and Responses to Muhammad Ali in 1960s Britain - Martin Johnes (The International Journal of the History of Sport, 2019)
Muhammad Ali fought in the UK three times in the 1960s, each time to the accompaniment of significant media coverage that made him into a public figure. On his first fight in 1963, his unusual personality both delighted and reviled. Many of the criticisms were rooted in a dislike of American culture but beneath them were also racial stereotypes that encouraged a view of him as brash and immature. By his second and third fights in 1966, he was a deeply controversial figure in the USA because of his conversion to Islam and opposition to the Vietnam War. Yet neither issue had the same significance in the UK and his British fan base grew, despite the way he also reminded some of the danger that British racial tensions might escalate in the way they had in America. Ali was also an inspiration to Britons of colour and those who believed in the need for radical challenges to the world’s problems. As such, he is an example of how ideas, fears and hopes around race relations were transnational and the need for its British historians to ensure their accounts are de-domesticised.